2013
DOI: 10.1177/0023677213476278
|View full text |Cite
|
Sign up to set email alerts
|

Group housing of male CD1 mice: Reflections from toxicity studies

Abstract: Owing to their naturally aggressive behaviour, male mice are often housed individually in toxicity studies. However, several publications advocate group-housing of mice to enable normal social behaviour and interactions between the animals. This refinement project aimed at facilitate group-housing in toxicity studies. A handling procedure, including key factors such as allocation into groups before sexual maturation, transfer of used nesting material into clean cages and avoidance of external changes, that mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…Thus, aggression levels increase with group size, particularly in excess of three individuals in a standard shoebox cage 23 . Establishing stable groups, such as keeping siblings or familiar mice together from weaning, generally decreases aggression 7,27 . Large differences in aggression also exist between strains, both in the resident-intruder test 28 and in the home cage 29 , indicating that there is a possible genetic component.…”
Section: What We Have Learned About Aggression In Laboratory Micementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, aggression levels increase with group size, particularly in excess of three individuals in a standard shoebox cage 23 . Establishing stable groups, such as keeping siblings or familiar mice together from weaning, generally decreases aggression 7,27 . Large differences in aggression also exist between strains, both in the resident-intruder test 28 and in the home cage 29 , indicating that there is a possible genetic component.…”
Section: What We Have Learned About Aggression In Laboratory Micementioning
confidence: 99%
“…Both injured and very aggressive mice are generally separated and may be euthanized. These problems could be avoided by housing all mice singly 7,8 , although this is clearly not optimal for welfare either. Ultimately, injuries, deaths and social isolation directly conflict with the 3Rs goals of reduction and refinement.…”
mentioning
confidence: 99%
“…Several studies have identified factors associated with aggression in mice [12][13][14][15] and some general husbandry recommendations have been suggested to decrease levels of aggression. Some examples are to keep mice in small groups (three animals have been suggested), to group animals at an age of 3-4 weeks, to keep siblings or familiar mice together, and to transfer nesting material at cage cleaning [13,16,17]. However, mice are not always kept according to these recommendations, and sometimes mice fight despite being kept according to them, emphasizing that the nature of aggression is complex.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of aggression in groups of male mice typically leads to two management solutions: (1) male mice are socially housed until a certain degree of aggression occurs and are then separated and housed individually until the end of the study 8 or (2) males are individually housed for the entire duration of a study 9 . The first approach has several detrimental consequences when fighting occurs, as animals might be severely injured or killed.…”
mentioning
confidence: 99%
“…Despite anecdotal reports on the successful use of the combinations of factors named above in long-term toxicological research 9 , neither original data, nor details on the housing conditions that prove beneficial effects have been published. Therefore, the aim of this experiment was to test the effects of different housing conditions and husbandry procedures on aggressive behavior and well-being of male mice.…”
mentioning
confidence: 99%